From Forest Preschool to Bush Kinder: An Inspirational Approach to Preschool Provision in Australia. Issue 4 (December 2014) - Elliott, Sue; Chancellor, Barbara
DRAWING INSPIRATION FROM EUROPEAN forest preschools, Westgarth Kindergarten instigated a Bush Kinder Pilot Program as an innovative response to the Australian Government's universal access directive to provide 15 hours of preschool per week for all four-year-olds. The preschool children at Westgarth Bush Kinder participated in a play-based child-centred program within their local Darebin Parklands each Wednesday with two kindergarten teachers. In total the children attended 12 hours of preschool per week at Westgarth Kindergarten (home kindergarten) and three hours per week at the Bush Kinder. This study examined how the pilot program addressed the vision of the kindergarten community and the efficacy of the service model as a response to the universal access directive. The positive impacts of the program for children, parents and teachers offer key findings for other kindergarten communities seeking alternative responses to universal access. The Westgarth Bush Kinder Pilot Program exceeded the expectations of all involved; the right people, in the right place, at the right time inspired this unique response.